2012
DOI: 10.1007/s00404-012-2226-5
|View full text |Cite
|
Sign up to set email alerts
|

p53 codon 72 polymorphism and endometriosis: a meta-analysis

Abstract: This meta-analysis suggests that p53 codon 72 Pro/Pro + Arg/Pro genotypes are associated with increased risk of endometriosis in Asian. To validate the association between p53 codon 72 polymorphism and endometriosis, further studies with larger participants worldwide are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
2
Order By: Relevance
“…This meta-analysis differs from a previous meta-analysis analyzing the relationship between the p53 codon 72 polymorphism and endometriosis risk performed by Jia et al (2012). Specifically, in the present report, 4 more studies (Bianco et al, 2011;Govatati et al, 2012;Paskulin et al, 2012;Ying et al, 2011), 1,196 more patients, and 1,299 more controls were included; and one study was excluded due to duplicate data (Hsieh & Lin, 2006).…”
Section: Test Of Associationcontrasting
confidence: 59%
“…This meta-analysis differs from a previous meta-analysis analyzing the relationship between the p53 codon 72 polymorphism and endometriosis risk performed by Jia et al (2012). Specifically, in the present report, 4 more studies (Bianco et al, 2011;Govatati et al, 2012;Paskulin et al, 2012;Ying et al, 2011), 1,196 more patients, and 1,299 more controls were included; and one study was excluded due to duplicate data (Hsieh & Lin, 2006).…”
Section: Test Of Associationcontrasting
confidence: 59%
“…Although two meta-analyses addressing the association between the TP53 codon 72 polymorphism and endometriosis risk have been published, this study's findings indicate that the TP53 codon 72 polymorphism is associated with endometriosis risk, especially in Asian and Latin American populations, which is in part in contrast to both Jia's and Song's results (Jia et al, 2012;Song and Lee, 2014). Compared with the previous studies, this current meta-analysis has several particular strengths.…”
Section: Discussioncontrasting
confidence: 61%
“…This polymorphism (rs1042522) shows a single nucleotide substitution of G to C, resulting in the shift of arginine to proline in the amino acidic sequence. Previously, two research groups conducted metaanalyses concerning this theme and presented the same conclusion that TP53 codon 72 polymorphism was associated with the endometriosis risk in Asian populations rather than overall and in Caucasian populations (Jia et al, 2012;Song and Lee, 2014). By including certain new cohorts (Camargo-Kosugi et al, 2014;Chan, 2013;Frare et al, 2013;Huang et al, 2013;Kang et al, 2004;Silva, 2012) and applying different approaches for subgroup analyses, this study conducted an updated meta-analysis in order to further clarify the association between TP53 codon 72 polymorphism and susceptibility of endometriosis.…”
Section: Introductionmentioning
confidence: 80%
“…A study performed in a Japanese population revealed that the Pro/Pro genotype at codon 72 was associated with increased risk of prostate cancer and its progression (35). Two separate meta-analyses by Jia et al (36) and Lao et al (37) suggested that the homozygote and heterozygote genotypes of Pro participated in the development of endometriosis in Asian and Caucasian populations. Analysis of this variant among an Iranian population revealed that the Arg genotype increased the risk of breast cancer while Pro served as a protective factor (38).…”
Section: Discussionmentioning
confidence: 99%